The Gen Z Student’s Styles In Learning English At Islamic Junior High School - Yunus, Aulia; Seftina, Ayumi; Fatimah, Dwi; Syaharani, Namira; Santoso, Didik (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study explores the learning styles of Generation Z students in the context of learning English at an Islamic Junior High School. Generation Z, characterized by its digital nativity and diverse learning preferences, presents unique challenges and opportunities for educators. The research employed qualitative methods to investigate how these students engage with English language learning, focusing on their preferred learning styles, technological integration, and cultural influences within an Islamic educational environment. Findings suggest that while digital tools are widely embraced, traditional pedagogical approaches remain influential. The study concludes with implications for educators to better cater to Gen Z's learning preferences while respecting the cultural and religious contexts of Islamic education.